Exploring sustainability careers in the fashion industry - Esch, Elizabeth D. (My University, 2025)
This research project explores job positions focused on sustainability in the fashion industry to better understand the knowledge and skills required for this career field. Two research questions are presented to meet this goal. (1) What jobs exist in the fashion industry where the primary responsibility of the position is to advance sustainability initiatives within the business? (2) What knowledge and skills relating to sustainability are required for individuals working in sustainability-focused careers in the fashion industry? Data was collected in two phases to answer these questions. The first phase gathered current job descriptions relating to positions associated with sustainable fashion, while the second phase interviewed industry professionals about their experiences working in sustainable fashion and what knowledge and skills are needed. To analyze the data, a qualitative approach was employed, utilizing In Vivo and Pattern coding. Results found that greater levels of resiliency are required, experience and industry allies are often of more value than high levels of education, and a wide variety of knowledge and skills are needed. There are many opportunities for future research, which include understanding the future of sustainability jobs in fashion, individuals’ motivations for advancing sustainability efforts, and exploring strategies for overcoming challenges and driving meaningful change within the fashion industry. Insights from this study aim to help individuals prepare for careers in sustainable fashion.
Keywords: Sustainability; Fashion; Education; Careers; What to know